INFLUENCE OF CODE OF POINT CHANGE ON INDIVIDUAL RHYTHMIC GYMNASTICS PERFORMANCE - Rebecca M. Freire-Maceiras; Elena Sierra- Palmeiro; María A Fernández-Villarino (Science of Gymnastics Journal, 2025)
The aim of this study was to analyse the effects of a rule change on the performance model of individual rhythmic gymnastics. For the study, the results of 572 competition routines were collected from two different world championships, each held under a different set of rules (2017-2021 and 2022-2024). The variables of the study included: the rules used at each championship, the score for body difficulty, the score for apparatus difficulty, the score for artistic execution, the score for technical execution and the final score. The main findings indicate that changing the scoring code leads to a significant change in the gymnasts' performance model, especially in terms of body and apparatus difficulty. The change in the scoring code equalised the partial contribution of each scoring aspect to the gymnasts' overall performance. With the previous code, the difficulty of the apparatus was more important than other aspects. With the current code, the contribution of all performance components is more balanced. The main conclusion is the need to change the routine composition and training model and to optimise the judges' evaluation parameters.